Aquatic adaptation of a laterally acquired pectin degradation pathway in marine gammaproteobacteria. (3rd April 2017) - Hehemann, Jan‐Hendrik; Truong, Le Van; Unfried, Frank; Welsch, Norma; Kabisch, Johannes; Heiden, Stefan E.; Junker, Sabryna; Becher, Dörte; Thürmer, Andrea; Daniel, Rolf; Amann, Rudolf; Schweder, Thomas
Summary: Mobile genomic islands distribute functional traits between microbes and habitats, yet it remains unclear how their proteins adapt to new environments. Here we used a comparative phylogenomic and proteomic approach to show that the marine bacterium Pseudoalteromonas haloplanktis ANT/505 acquired a genomic island with a functional pathway for pectin catabolism. Bioinformatics and biochemical experiments revealed that this pathway encodes a series of carbohydrate‐active enzymes including two multi‐modular pectate lyases, PelA and PelB. PelA is a large enzyme with a polysaccharide lyase family 1 (PL1) domain and a carbohydrate esterase family 8 domain, and PelB contains a PL1 domain and two carbohydrate‐binding domains of family 13. Comparative phylogenomic analyses indicate that the pathway was most likely acquired from terrestrial microbes, yet we observed multi‐modular orthologues only in marine bacteria. Proteomic experiments showed that P. haloplanktis ANT/505 secretes both pectate lyases into the environment in the presence of pectin. These multi‐modular enzymes may therefore represent a marine innovation that enhances physical interaction with pectins to reduce loss of substrate and enzymes by diffusion. Our results revealed that marine bacteria can catabolize pectin, and highlight enzyme fusion as a potential adaptation that may facilitate microbial consumption of polymeric substrates in aquatic environments.